Efforts To Increase the Number of Customers Transacting at The Kimia Farma Malang Clinical Laboratory with The Blue Ocean Strategy Approach - Anisa Ika Rahmania (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
PT. Kimia Farma Diagnostik is a subsidiary of PT. Chemical Pharmacies Pharmacies. KFD's business scope is clinical and clinical laboratories. This research is located in the clinical laboratory of Kimia Farma Malang. The revenue of the Malang pharma chemical laboratory in 2020 tends to be unstable and the number of customers has fallen. Based on the comparison of competitors, it can be seen that the competitor's facilities are superior with a larger number of outlets. Due to the limited facilities and human resources owned, the laboratory must have a strategy to be able to compete. This research uses a qualitative descriptive method in the form of a case study with direct observation, in-depth interviews, and document review. The interview results are translated into a SWOT analysis and then a four-step framework is created, namely eliminate, reduce, raise, and create. Then create a canvas strategy and then create an innovation strategy. After that, recommendations were prepared to increase the number of customers who transacted at the Malang pharma chemistry clinic laboratory. The results of this study show strategic innovations that are close to the Blue Ocean Strategy, namely the differentiation strategy of facilities and infrastructure, product development strategies (genomic laboratories, DNA test services and home services), Information Technology (IT) strategies, market extension strategies for laboratory quality to international standardization, market penetration strategies for customers (loyal customers and retain customers).